2019
DOI: 10.26803/ijlter.18.10.1
|View full text |Cite
|
Sign up to set email alerts
|

Burnout of Primary Teachers in Qatar Government Schools during an Era of Educational Reform

Abstract: This study examined the burnout levels of a broad crosssectional sample of primary school teachers (n=1657) from Qatar within the three domains of the burnout syndrome: Emotional Exhaustion (EE), Depersonalization (DP), and Personal Accomplishment (PA). Statistical analysis results indicated high levels of burnout reported by the participants (52.2%) within the core dimension of burnout -Emotional Exhaustion (EE) dimension, indicating a high level of emotional overextension and exhaustion. Relatively low level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…Several female participants in this study expressed their feelings of stress or being exhausted working at government schools, which is in line with what was reported previously by (Alloh et al 2019) when female novice teachers in Qatari primary schools with less than five years of experience were scored high levels in their Emotional Exhaustion burnout (EE). In this study, it seems that male teachers suffered less from the burnout levels, feeling of exhaustion, and depression, which align with the findings of (Boström, Björklund, Bergström, Nybergh, Schäfer Elinder, Stigmar & Kwak, 2020), female participants were significantly more stressed than their male colleagues, with 20.2% of female teachers reported "very much stress" compared to 4.5% of male teachers.…”
Section: Challengessupporting
confidence: 91%
See 2 more Smart Citations
“…Several female participants in this study expressed their feelings of stress or being exhausted working at government schools, which is in line with what was reported previously by (Alloh et al 2019) when female novice teachers in Qatari primary schools with less than five years of experience were scored high levels in their Emotional Exhaustion burnout (EE). In this study, it seems that male teachers suffered less from the burnout levels, feeling of exhaustion, and depression, which align with the findings of (Boström, Björklund, Bergström, Nybergh, Schäfer Elinder, Stigmar & Kwak, 2020), female participants were significantly more stressed than their male colleagues, with 20.2% of female teachers reported "very much stress" compared to 4.5% of male teachers.…”
Section: Challengessupporting
confidence: 91%
“…Nevertheless, Qatar's novice teachers are being expected to bear the same teaching loads and responsibilities as their more experienced colleagues (Alloh, Hasan, Du & Romanowski, 2019). This study demonstrated that novice (less than five years of teaching experience) and experienced (between five or more years of teaching experience) teachers reported high levels of EE burnout.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Teachers who do not care about their students may experience burnout or physical or mental exhaustion/saturation due to increased task demands (Alloh et al, 2019).It is natural because the work of the ministry requires more energy, time and thought. Therefore, CRE teachers need to have sufficient rest time and look back at the purpose of vocation as a CRE teacher.…”
Section: Caring Teachersmentioning
confidence: 99%
“…Within this theme around 48% of the factors contributed to various categories of stress. They were multi-tasking (Gold et al, 2009), workload (Gold et al, 2009Simbula et al, 2012;Vazi et al, 2013;Vesely et al, 2013;Bermejo-Toro et al, 2015;Desrumaux et al, 2015;Yerdelen et al, 2016;Helms-Lorenz & Maulana, 2016;Skaalvik & Skaalvik, 2017;Alvarado & Bretones, 2018;Alloh et al, 2019;Braun et al, 2019;Soykan et al, 2019;Brady & Wilson, 2020;Carroll et al, 2020;Farley & Chamberlain, 2021;Hepburn et al, 2021a;Ibrahim et al, 2021;Tebben et al, 2021;Billett et al, 2022), lack of professional recognition and appreciation, administration overload, role conflict, poor working condition, time pressure, lack of recourses and technology, appeared as organisational factors which contributed to teachers' stress. Workload was the prominent category which was recorded in most of the studies to be the key factor for emotional exhaustion among teachers (Bower & Carroll, 2017) and burn out (Chang, 2009).…”
Section: Organisational Stress Factorsmentioning
confidence: 99%